Analisa Pengaruh Person-Environment Fit terhadap Kepuasan Kerja - , Angeline Dian Paramita ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Employee job satisfaction can very much depend on the work conditions itself and can be considered as one of important matters in work force. There is a statement that a satisfied employee is a better employee, and sometimes is called a more productive employee. The basic of person-environment fit concept is to indicate any congruency between a personâs characteristics with his or her environment that can be posotive both for the person and the environment. When the environment variable is the work environment, then it can be said that one of significant results from person-environment fit is job satisfaction. Object of the research is employees of a reasearch company with total sample of 50 employees. A descriptive approach is used in this research in order to explain the impact of independent variable (person-environment fit) toward job satisfaction. Results indicated that person-environment fit do not have any significant impact towards job satisfaction. Asumption of that person-environment fit will influence job satisfaction also is not proven. Although person-environment fit is considered to be importation for one personâs characteristic fitness to the environment will provide a positive result, it is not the most important or significant matter.